2017
DOI: 10.1016/j.neuropharm.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

αO-Conotoxin GeXIVA disulfide bond isomers exhibit differential sensitivity for various nicotinic acetylcholine receptors but retain potency and selectivity for the human α9α10 subtype

Abstract: Nicotinic acetylcholine receptor (nAChR) subtypes exhibit distinct neuropharmacological properties that are involved in a range of neuropathological conditions, including pain, addiction, epilepsy, autism, schizophrenia, Tourette’s syndrome, Alzheimer’s and Parkinson’s diseases, as well as many types of cancer. The α9α10 nAChR is a potential target in chronic pain, wound healing, the pathophysiology of the auditory system, and breast and lung cancers. αO-conotoxin GeXIVA is a potent antagonist of rat α9α10 nAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 46 publications
6
38
0
Order By: Relevance
“…As previously discussed, RgIA4 has been shown to be an effective analgesic and prophylactic in the oxaliplatin model of neuropathic pain . Additional conopeptides have also been recently discovered that selectively target α9‐containing nAChRs . These peptides are structurally unrelated to RgIA and Vc1.1 yet analgesic, further validating α9‐containing nAChRs as therapeutic targets for the treatment of neuropathic pain.…”
Section: α9 Nachrs In Neuropathic Pain and Inflammationmentioning
confidence: 90%
“…As previously discussed, RgIA4 has been shown to be an effective analgesic and prophylactic in the oxaliplatin model of neuropathic pain . Additional conopeptides have also been recently discovered that selectively target α9‐containing nAChRs . These peptides are structurally unrelated to RgIA and Vc1.1 yet analgesic, further validating α9‐containing nAChRs as therapeutic targets for the treatment of neuropathic pain.…”
Section: α9 Nachrs In Neuropathic Pain and Inflammationmentioning
confidence: 90%
“…The previous research showed that GeXIVA[1,2] and GeXIVA[1,4] (Figure ) were the most active isomers with similar IC 50 s on rat and human α9α10 nAChRs, GeXIVA[1,3] was the least active isomer . GeXIVA[1,2] and GeXIVA[1,4] (Figure ) had a similar IC 50 of 4.6 and 7 n m at rat α9α10 nAChRs, respectively.…”
Section: Introductionmentioning
confidence: 85%
“…For human α9α10 nAChRs, GeXIVA[1,2] and GeXIVA[1,4] had a similar IC 50 of 20 and 47 n m , respectively. While GeXIVA[1,3] displayed the lowest potency with an IC 50 of 116 n m at human α9α10 nAChRs . The most potent isomer was found to be GeXIVA[1,2], which blocked human α9α10 nAChRs almost completely at 100 n m (~100% inhibition), GeXIVA[1,4] was the second with a 67% inhibition at 100 n m .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The α‐conotoxin AuIB isomers have substantial difference in their secondary structures and bioactivity, especially in their way of inhibiting nicotinic acetylcholine receptors (nAChRs) . Structure and activity relationship for the disulfide isomers of αO‐conotoxin GeXIVA, μ‐conotoxins KIIIA, μ‐conotoxin KIIIB, μ‐conotoxin PIIIA, and α‐conotoxin GI has been investigated, and the results suggested that in some cases, certain disulfide isomers could retain the bioactivity of the native peptide despite of their significantly varied secondary structures.…”
Section: Introductionmentioning
confidence: 99%